The Place Of The Thermo-Tolǵov Genre In The Repertoire Of KíyasZhírovKayratdinov - Ernazarovna, YaxiyaevaShaxnoza (International Journal Of Literature And Languages, 2026)
This article discusses the role of terma-tolgovs, which are expressed in Karakalpak folklore, in the formation of the Qiyas jirov repertoire.